Telehealth for healthy gestational weight gain among overweight pregnant women: A systematic review - Chotimah, Kusnul; Has, Eka Mishbahatul M.; Rachmawati, Praba Diyan (Universitas Airlangga, 2024)
Introduction: Excessive Gestational Weight Gain (GWG) is associated with various complications during pregnancy and childbirth. In contrast, digital interventions like telehealth offer cost-effective solutions with broader accessibility. Therefore, our outcomes are to analyze the effectiveness of telehealth interventions for healthy GWG among overweight and obese pregnant women and to know which features are needed in telehealth for healthier GWG.Methods: We undertook a systematic review to address the objectives mentioned above. Initially, we employed the keywords telehealth, pregnant women, and overweight, which were subsequently refined using Medical Subject Headings provided by the National Center for Biotechnology Information. To identify relevant articles, we searched six databases”Scopus, SAGE Journals, Web of Science, PubMed, ScienceDirect, and ProQuest.Results: We included 15 articles in this review according to the criteria. Eleven papers show a positive effect of telehealth in promoting healthy GWG. Telehealth encompasses various functionalities, such as providing information, push notifications, self-monitoring, and feedback features related to gestational weight gain (GWG), maintaining a healthy diet, engaging in physical activity, receiving reminders, managing stress, and setting goals. On the other hand, four papers show no significant difference between telehealth and regular interventions.Conclusions: Telehealth is alternatively effective to use as an additional intervention to promote healthier GWG in overweight pregnant women. Keywords: gestational weight gain; overweight; pregnant women; telemedicine